Analysis of immune complexes in synovial effusions of patients with rheumatoid arthritis. - Male, D (1980)
Immune complexes were isolated from the synovial effusions of patients with seropositive definite or classical rheumatoid arthritis by centrifugation over a sucrose-polyethylene glycol gradient. Physiochemical and immunochemical analysis showed IgG and IgM to be the predominant molecular species with lesser amounts of Clq and moderate amounts of IgA and activated C4 and C3. Very low concentrations of Clr, Cls, factor B and beta 2-microglobulin were detected. Trace amounts of four other components totalling less than 4% of the total protein, were seen and their molecular weights established. Reasons were advanced for thinking that fibrinogen, human serum albumin and alpha 2-macroglobulin were only secondarily associated with the complexes. The data are consistent with the hypothesis that IgG is the main, if not the only antigen, responsible for provoking and maintaining the pathological changes in rheumatoid arthritis.